Vegetating mine tailings: The benefits of using non-native species in the remediation of a bauxite residue site in Jamaica - Williams, J; Williams, L; Evans, K; Siebring, E; Carper, J; Rasmussen, Z; Leclerc, D (Mine Closure 2023: 16th International Conference on Mine Closure, 2023)
The impact of non-native plant species, particularly invasive species, on biodiversity has been investigated and documented for decades and the general consensus is that they can pose risks and have a negative effect on native flora and fauna. However, there can be ecological and conservational benefits from using non-native plant species in the mine closure process, where remediation of process waste within a defined time period is often a requirement and presents greater challenges compared to a normal mine site. Initial remediation work on Rio Tinto’s bauxite residue sites in Jamaica commenced in the mid-2000s, and with the majority of the vegetation work now completed this paper aims to present some of the advantages of using non-native species in the remediation programme undertaken at a bauxite residue disposal site. In addition, the paper discusses the use of non-native plants in mine closure projects generally, local challenges surrounding the awareness and management of species that are now considered invasive, and some direction when local legislation is absent. The aim of this paper is to offer another perspective to the general view of negative impact of non-native species and demonstrate how some non-native, and even invasive plants, could play a beneficial role in certain cases in the field of tailings site closure.
Keywords: mine closure; mine tailings; bauxite residue; red mud; revegetation; non-native species; invasive species; biodiversity